The concept of education in the expression of "hutang orang tua" towards children and its relevance to the Profile of Pelajar Pancasila - Tarwiyani, Tri; Karnesyah, Ade; Sari, Devi Liana; Yanti, Fitri; Santi. T, Mei (CAHAYA PENDIDIKAN, 2023)
Education is a basic thing that every human being needs. Education is also a way to internalize the various values and views held and upheld by a group or society. If in education the Indonesian nation proclaimed "Pancasila Student Profile", then the Malay community has the expression "Parents' debt". The phrase "parental debt" in this case is the debt parents owe to their children, where one of the debts is related to education. Both the phrase "Parents' debt" and the concept contained in "Pancasila Student Profile", indirectly indicate the importance of education for society. This research aims to reveal the meaning behind the expression "parents' debt", formulate the educational concept behind the expression "parents' debt", and find out the relevance of the Malay people's expression "Parents' debt" to the educational concept launched by the Indonesian government, namely "Pancasila Student Profile".This research is a literature study with a philosophical hermeneutic method. The methodical elements of this research include deduction-induction, holistic, historical continuity, language analysis, heuristics, and description. This research came up with the following results: a) the expression "hutang orang tua" contains a person's obligations towards their children, where one of these obligations is related to the educational provisions that parents must provide to their children; b) the concept of education contained in the expression "hutang orang tua" includes two aspects, spiritual and physical, because both, physical and spiritual, are one unit with the aim of giving birth to "anak bertuah"; c) the values that constitute the content of education in Malay society have similarities with the "Profil Pelajar Pancasila" such as the values of faith and devotion to Almighty God, good character, mutual cooperation and tolerance. This shows that the values contained in the "Profil Pelajar Pancasila" have essentially existed and been developed in Indonesian society. The novelty in this paper is apart from the relevance of the expression "hutang orang tua" to the Profil Pelajar Pancasila, the novelty is also related to the discovery of the meaning behind the expression "hutang orang tua" and the formulation of the educational concept behind the expression "hutang orang tua".